Corneal cross-linking in a 10-year-old child with stage III keratoconus - Abbondanza, Marco; Felice, Valentina De; Abbondanza, Gabriele (Nepalese Journal of Ophthalmology, 2017)
Background: Keratoconus is a corneal dystrophy characterized by progressive thinning, conical shape of the cornea and irregular astigmatism. It is particularly insidious when it occurs in very young patients. Case: We report the case of a 10-year-old child with an aggressive stage III keratoconus, who was suggested to undergo a Penetrating Keratoplasty. We performed Corneal Collagen Cross-linking with epithelium removal instead, which was successful in arresting the rapid progression of keratoconus. Observations: Eighteen months later, Kmax had decreased by 1.3 D, astigmatism by 0.8 D, thinnest pachimetry had improved by 69 μm and CDVA was 20/32. Conclusion: This case confirms that Corneal Collagen Cross-linking is a safe and effective procedure for the treatment of keratoconus even in its aggressive forms. We encourage ophthalmic surgeons to favor conservative treatments when dealing with very young patients.